Versicolorin A enhances the genotoxicity of aflatoxin B1 in human liver cells by inducing the transactivation of the Ah-receptor. (July 2021) - Budin, Clémence; Man, Hai-Yen; Al-Ayoubi, Carine; Puel, Sylvie; van Vugt-Lussenburg, Barbara M.A.; Brouwer, Abraham; Oswald, Isabelle P.; van der Burg, Bart; Soler, Laura
Abstract: Aflatoxins are a group of mycotoxins that have major adverse effects on human health. Aflatoxin B1 (AFB1) is the most important aflatoxin and a potent carcinogen once converted into a DNA-reactive form by cytochrome P450 enzymes (CYP450). AFB1 biosynthesis involves the formation of Versicolorin A (VerA) which shares structural similarities with AFB1 and can be found in contaminated commodities, often co-occurring with AFB1. This study investigated and compared the toxicity of VerA and AFB1, alone or in combination, in HepG2 human liver cells. Our results show that both toxins have similar cytotoxic effects and are genotoxic although, unlike AFB1, the main genotoxic mechanism of VerA does not involve the formation of DNA double-strand breaks. Additionally, we show that VerA activates the aryl hydrocarbon receptor (AhR) and significantly induce the expression of the CYP450-1A1 (CYP1A1) while AFB1 did not induce AhR-dependent CYP1A1 activation. Combination of VerA with AFB1 resulted in enhanced genotoxic effects, suggesting that AhR-activation by VerA influences AFB1 genotoxicity by promoting its bioactivation by CYP450s to a highly DNA-reactive metabolite. Our results emphasize the need for expanding the toxicological knowledge regarding mycotoxin biosynthetic precursors to identify those who may pose, directly or indirectly, a threat to human health. Highlights: VerA and AFB1 are cyto- and genotoxic to human HepG2 hepatocytes. Genotoxicity was evaluated with p53 CALUX assays, yH2AX-ICW and p53 Ser15-P. VerA can activate the AhR and induce the transcription of CYP1A1. Combination of AFB1 and VerA results in enhanced cyto- and genotoxic effects. Significant effects were observed at concentrations ≤ 1 μM.